2002
DOI: 10.1021/ja0202006
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Polymer Chemistry:  Self-Assembling Dendrimers Using the DDA·AAD (GC-like) Hydrogen Bonding Motif

Abstract: Heterocyclic unit 2 containing complementary donor-donor-acceptor (DDA) and acceptor-acceptor-donor (AAD) hydrogen bonding arrays at an angle of about 60 degrees was designed to self-assemble into a hexamer. To investigate whether this unit could self-assemble dendrimers, the 2,8-diamino-2-N-ethylpyrimido-(4,5-b)(1,8)naphthyridine-3H-4-one subunit was synthesized with a first (2a), second (2b), and third generation (2c) Fréchet-type dendron attached to the 8-amino group. The synthesis of 2a-c was accomplished … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
87
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(88 citation statements)
references
References 25 publications
0
87
0
1
Order By: Relevance
“…[10][11][12] Although these non-covalent associations are usually weaker and reversible when compared to most covalent interactions, ionically driven attractions exhibiting multiple interactions per specie can result in very strong binding energies. [13,14] Incorporation of these interactions has also facilitated the construction of materials and devices for applications in photonics, [15] electronics, [16] conducting polymers, [17] and polyelectrolytes.[18]Herein, we report the ion-promoted, automorphogenic, [19] and stoichiometric self-assembly of nanoscale composite fibers using a structurally rigid hexameric macrocycle [( 1 12þ )(PF (1) 9 (3)] m . These polyanionic dense-packed counterions led to ion pair superstructures in which the randomness of singly-charged counterions was eliminated.…”
mentioning
confidence: 99%
“…[10][11][12] Although these non-covalent associations are usually weaker and reversible when compared to most covalent interactions, ionically driven attractions exhibiting multiple interactions per specie can result in very strong binding energies. [13,14] Incorporation of these interactions has also facilitated the construction of materials and devices for applications in photonics, [15] electronics, [16] conducting polymers, [17] and polyelectrolytes.[18]Herein, we report the ion-promoted, automorphogenic, [19] and stoichiometric self-assembly of nanoscale composite fibers using a structurally rigid hexameric macrocycle [( 1 12þ )(PF (1) 9 (3)] m . These polyanionic dense-packed counterions led to ion pair superstructures in which the randomness of singly-charged counterions was eliminated.…”
mentioning
confidence: 99%
“…and for a full discussion the reader is directed to a number of excellent reviews In an attempt to provide this type of assembly with additional specificity and control, Zimmerman and co-workers have also developed supramolecular dendrimers which use a DDA . AAD hydrogen bonding motif (D: hydrogen-bond donor; A: hydrogen bond acceptor) to assemble individual dendrons into hexameric rosettes [6]. All studies were consistent with a cooperative aggregation process, and it was observed that decreasing the concentration, increasing the temperature or adding a competitive solvent shifted the equilibrium back from hexameric rosette towards monomer -clearly illustrating the reversibility of this type of assembly process.…”
Section: Introductionmentioning
confidence: 68%
“…41,42 For example, Zimmerman and co-workers find that I-46 -G1 which contains DAA and DDA H-bonding faces with 60˚ relative orientation undergoes self-assembly to yield hexamer (I-46 -G1) 6 (Scheme I-11) as evidence by size exclusion chromatography (SEC). Similarly, dimeric compound I-47 -G3 with its self-complementary DDAA faces forms an exceptionally stable cyclic hexamer (I- 6 by H-bonding interactions.…”
Section: Zn(ii)mentioning
confidence: 99%